Room-Temperature Electrical Field-Enhanced Ultrafast Switch in Organic Microcavity Polariton Condensates - De, Jianbo; Ma, Xuekai; Yin, Fan; Ren, Jiahuan; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing; Malpuech, Guillaume; Solnyshkov, Dmitry (Journal of the American Chemical Society (JACS))
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

A High-Rate Two-Dimensional Polyarylimide Covalent Organic Framework Anode for Aqueous Zn-Ion Energy Storage Devices - Yu, Minghao; Chandrasekhar, Naisa; Kormath Madam Raghupathy, Ramya; Ly, Khoa Hoang; Zhang, Haozhe; Dmitrieva, Evgenia; Liang, Chaolun; Lu, Xihong; Kühne, Thomas; Mirhosseini, S. Hossein; Weidinger, Inez M.; Feng, Xinliang (Journal of the American Chemical Society)
Rechargeable aqueous Zn-ion energy storage devices are promising candidates for next-generation energy storage technologies. However, the lack of highly reversible Zn2+-storage anode materials with low potential windows remains a primary concern. Here, we report a two-dimensional polyarylimide covalent organic framework (PI-COF) anode with high-kinetics Zn2+-storage capability. The well-organized pore channels of PI-COF allow the high accessibility of the build-in redox-active carbonyl groups and efficient ion diffusion with a low energy barrier. The constructed PI-COF anode exhibits a specific capacity (332 C g–1 or 92 mAh g–1 at 0.7 A g–1), a high rate capability (79.8% at 7 A g–1), and a long cycle life (85% over 4000 cycles). In situ Raman investigation and first-principle calculations clarify the two-step Zn2+-storage mechanism, in which imide carbonyl groups reversibly form negatively charged enolates. Dendrite-free full Zn-ion devices are fabricated by coupling PI-COF anodes with MnO2 cathodes, delivering excellent energy densities (23.9 ∼ 66.5 Wh kg–1) and supercapacitor-level power densities (133 ∼ 4782 W kg–1). This study demonstrates the feasibility of covalent organic framework as Zn2+-storage anodes and shows a promising prospect for constructing reliable aqueous energy storage devices.

Encoding Metal–Cation Arrangements in Metal–Organic Frameworks for Programming the Composition of Electrocatalytically Active Multimetal Oxides - Castillo-Blas, Celia; Lopez Salas, Nieves; Gutiérrez, María C.; Puente-Orench, Inés; Gutiérrez-Puebla, Enrique; Ferrer, M. Luisa; Monge, M. Ángeles; Gándara, Felipe (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Frustrated Lewis Pair Catalyzed Hydrogenation of Amides: Halides as Active Lewis Base in the Metal-Free Hydrogen Activation - Sitte, Nikolai A.; Bursch, Markus; Grimme, Stefan; Paradies, Jan (Journal of the American Chemical Society)

Intradomain Allosteric Network Modulates Calcium Affinity of the C-Type Lectin Receptor Langerin - Hanske, Jonas; Aleksić, Stevan; Ballaschk, Martin; Jurk, Marcel; Shanina, Elena; Beerbaum, Monika; Schmieder, Peter; Keller, Bettina G.; Rademacher, Christoph (Journal of the American Chemical Society)
Keywords: pc2-ressources

Charge Photogeneration in Donor–Acceptor Conjugated Materials: Influence of Excess Excitation Energy and Chain Length - Tautz, Raphael; Da Como, Enrico; Wiebeler, Christian; Soavi, Giancarlo; Dumsch, Ines; Fröhlich, Nils; Grancini, Giulia; Allard, Sybille; Scherf, Ullrich; Cerullo, Giulio; Schumacher, Stefan; Feldmann, Jochen (Journal of the American Chemical Society)

Activation of Surface Hydroxyl Groups by Modification of H-Terminated Si(111) Surfaces - Thissen, Peter; Peixoto, Tatiana; Longo, Roberto C.; Peng, Weina; Schmidt, Wolf Gero; Cho, Kyeongjae; Chabal, Yves J. (Journal of the American Chemical Society)

Paramagnetic Palladacycles with PdIIICenters Are Highly Active Catalysts for Asymmetric Aza-Claisen Rearrangements - Eitel, Simon H.; Bauer, Matthias; Schweinfurth, David; Deibel, Naina; Sarkar, Biprajit; Kelm, Harald; Krüger, Hans-Jörg; Frey, Wolfgang; Peters, René (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

All-Liquid Photonic Microcavity Stabilized by Quantum Dots - Yim, Tae-Jin; Zentgraf, Thomas; Min, Bumki; Zhang, Xiang (Journal of the American Chemical Society)

Accessing Ultrashort Reaction Times in Particle Formation with SAXS Experiments: ZnS Precipitation on the Microsecond Time Scale - Schmidt, Wolfgang; Bussian, Patrick; Lindén, Mika; Amenitsch, Heinz; Agren, Patrik; Tiemann, Michael; Schüth, Ferdi (Journal of the American Chemical Society)
Precipitation of zinc sulfide particles is a very rapid process, and monitoring of the particle growth is experimentally very demanding. Applying a liquid jet flow cell, we were able to follow zinc sulfide particle formation on time scales down to 10−5 s. The flow cell was designed in such a way that data acquisition on the microsecond time scale was possible under steady-state conditions along a liquid jet (tubular reactor concept), allowing SAXS data accumulation over a time scale of minutes. We were able to monitor the growth of zinc sulfide particles and found experimental evidence for very rapid particle aggregation processes within the liquid jet. Under the experimental conditions the particle growth is controlled by mass transfer: i.e., the diffusion of the hydrogen sulfide into the liquid jet.

Biomimetic Synthesis of Resorcylate Natural Products Utilizing Late Stage Aromatization: Concise Total Syntheses of the Marine Antifungal Agents 15G256ι and 15G256β - Navarro, Ismael; Basset, Jean-François; Hebbe, Séverine; Major, Sarah M.; Werner, Thomas; Howsham, Catherine; Bräckow, Jan; Barrett, Anthony G. M. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Trapping Metal-Organic Framework Nanocrystals: An in-Situ Time-Resolved Light Scattering Study on the Crystal Growth of MOF-5 in Solution - Hermes, Stephan; Witte, Thomas; Hikov, Todor; Zacher, Denise; Bahnmüller, Stefan; Langstein, Gerhard; Huber, Klaus; Fischer, Roland A. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Controlled Formation of Ag Nanoparticles by Means of Long-Chain Sodium Polyacrylates in Dilute Solution - Huber, Klaus; Witte, Thomas; Hollmann, Jutta; Keuker-Baumann, Susanne (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Ordered Mesoporous Magnesium Oxide with High Thermal Stability Synthesized by Exotemplating Using CMK-3 Carbon - Roggenbuck, Jan; Tiemann, Michael (Journal of the American Chemical Society)
Periodically ordered mesoporous magnesium oxides were synthesized by utilization of mesoporous CMK-3 carbon as exotemplate. The products exhibit high thermal stability and basic properties, which makes them promising for application in heterogeneous basic catalysis.

Formation of Branched Calixarene AggregatesA Time-Resolved Static Light Scattering Study - Witte, Thomas; Decker, Björn; Mattay, Jochen; Huber, Klaus (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis